2015
DOI: 10.1104/pp.15.00278
|View full text |Cite
|
Sign up to set email alerts
|

The Barley Powdery Mildew Candidate Secreted Effector Protein CSEP0105 Inhibits the Chaperone Activity of a Small Heat Shock Protein  

Abstract: Pathogens secrete effector proteins to establish a successful interaction with their host. Here, we describe two barley (Hordeum vulgare) powdery mildew candidate secreted effector proteins, CSEP0105 and CSEP0162, which contribute to pathogen success and appear to be required during or after haustorial formation. Silencing of either CSEP using host-induced gene silencing significantly reduced the fungal haustorial formation rate. Interestingly, both CSEPs interact with the barley small heat shock proteins, Hsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 71 publications
6
100
0
Order By: Relevance
“…The present study was initially meant to analyse the subcellular localisation of CSEPs in barley leaf epidermal cells. Serendipitously, however, our observations instead confirmed our previous finding (Ahmed et al, ) that proteins often are translocated from the host cytosol, across the EHM, into the EHMx. Being an entirely unstudied phenomenon, we looked further into it and found interesting details on protein properties influencing uptake into the EHMx.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…The present study was initially meant to analyse the subcellular localisation of CSEPs in barley leaf epidermal cells. Serendipitously, however, our observations instead confirmed our previous finding (Ahmed et al, ) that proteins often are translocated from the host cytosol, across the EHM, into the EHMx. Being an entirely unstudied phenomenon, we looked further into it and found interesting details on protein properties influencing uptake into the EHMx.…”
Section: Introductionsupporting
confidence: 88%
“…When expressing free mYFP in the plant cytosol, ROI1/ROI2 equals 2.86 (mean of 53 cells; SE, 0.218). Although this indicated that intact proteins are able to cross the EHM, our previous study also demonstrated that certain proteins did not localise to the EHMx, as found for mYFP‐CSEP0105 (Ahmed et al, ). Here, we expanded the analysis and examined mYFP fusions of 11 Bgh CSEPs without signal peptides, thus forcing their targeting to the cytosol.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Genomic and proteomic studies have identified about 540 Blumeria effector candidates (BEC) or candidate secreted effector proteins (CSEP) (Bindschedler et al 2011;Kusch et al 2014;Pedersen et al 2012;Spanu et al 2010). A small number of these have been characterized (Ahmed et al 2015;Pliego et al 2013;Schmidt et al 2014;Zhang et al 2012), but the molecular mechanisms by which effectors manipulate host processes to promote colonization are still poorly understood.…”
mentioning
confidence: 99%